Hakikat Ketentuan Transisional dalam Pembentukan Peraturan Perundang-undangan - Rakia, Alwiyah Sakti Ramdhon Syah; Simanjuntak, Kristi Warista; Hidaya, Wahab Aznul; Darmawansya, Andi (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2021)
In the process of drafting regulations, transitional provisions are used in order to overcome the legal vacuum, legal certainty, legal protection, and regulate other matters of a transitional nature. In terms of nomenclature, transitional provisions are referred to by different terms but are considered to have the same meaning. However, the terms of the transitional provisions have certain differences. This study aims to answer the nature of the transitional provisions in every formation of legislation, as well as the status of meaning between the terms “Ketentuan Peralihan” and “Aturan Peralihan” which have the same meaning status in the system of forming legislations. The results of this study indicate that the preparation of the “Transitional Provisions” material in the Appendix to Law Number 15 of 2019 is not adequately used in the preparation of “Aturan Peralihan” in the constitution. This is because the essence of the preparation of transitional provisions in the constitution is not only in order to overcome the legal vacuum, legal certainty, legal protection, and regulate other matters of a transitional nature, but also because of the transfer of power.